Simulation of Electronic Structure of Aluminum Phosphide Nanocrystals Using Ab Initio Large Unit Cell Method - Hamad R. Jappor; Zeyad Adnan Saleh; Mudar A. Abdulsattar (Advances in Materials Science and Engineering)
Ab initio restricted Hartree-Fock method coupled with the large unit cell method is used to determine the electronic structure and physical properties of aluminum phosphide (AlP) nanocrystals between 216 and 1000 atoms with sizes ranging up to about 3 nm in diameter. Core and surface parts with different sizes are investigated. Investigated properties include total energy, cohesive energy, energy gap, valence band width, ionicity, and degeneracy of energy levels. The oxygenated (001)-(1×1) facet that expands with larger sizes of nanocrystals is investigated to determine the rule of the surface in nanocrystals electronic structure. Results revealed that electronic properties converge to some limit as the size of the large unit cell increases and that the 216 core atoms approaches bulk of Aluminum phosphide material in several properties. Increasing nanocrystals size also resulted in a decrease in lattice constant, increase of core cohesive energy (absolute value), increase of core energy gap, increase of core valence band width and decrease of ionicity. Valence and conduction bands are wider on the surface due to splitting and oxygen atoms. The method also shows fluctuations in the converged energy gap, valence band width and cohesive energy of core part of nanocrystals duo to shape variation.